Students' Views of TikTok as English Language Learning Resource: A Qualitative Approach - Ayudia Fauziah; Pratolo, Bambang Widi (Institut Agama Islam Negeri Palopo, 2025)
This study aimed to explore students' perceptions of using TikTok as a resource for learning English. The research design utilized was qualitative research with a case study approach, and the data were collected through interview transcripts and documents. The participants in this study were students from SMKN 1 Bantul and Universitas Ahmad Dahlan, who were selected purposely. The results of the descriptive analysis showed that most students had positive perceptions of using TikTok to learn English. TikTok improved students' English language skills, particularly pronunciation, vocabulary, and speaking. Students noted that TikTok provides diverse English content, allowing them to learn interactively through features such as duets and stitches. Additionally, TikTok's format of short, engaging videos helps maintain attention and makes learning enjoyable. However, challenges such as content accuracy and informal language usage were identified. Overall, TikTok has the potential to be a valuable tool in English language education, complementing traditional methods and engaging students in a dynamic learning process.